MicroRNA-18a promotes hepatocellular carcinoma proliferation, migration, and invasion by targeting Bcl2L10 - Wang X (OncoTargets and Therapy, 2018)
Xiaodong Wang,1 Jian Lu,1 Jisen Cao,2 Bozhao Ma,1 Chao Gao,1 Feng Qi1 1Department of General Surgery, Tianjin Medical University General Hospital, Tianjin, China; 2Department of Hepatobiliary Surgery, Tianjin Third Center Hospital, Tianjin, China Background: Hepatocellular carcinoma (HCC) is known to feature several microRNA dysregulations. This study aimed to determine and investigate the prognostic value of microRNA (miRNA/miR)-18a and its role in regulating the progression of HCC.Methods: miR-18a expressions in human HCC tissues, pair-matched adjacent normal liver tissues as well as in HCC cell lines were determined by quantitative real-time PCR. The prognostic value of miR-18a was determined using Kaplan–Meier survival analysis and multivariable Cox regression assay. The ability of miR-18a in promoting HCC progression was verified in vitro.Results: miR-18a expressions in HCC tissues and cells were more than twice those of the normal control group (P<0.05). miR-18a expression was associated with the alpha-fetoprotein (AFP) level, TNM stage, tumor size, and intrahepatic vascular invasion (P<0.05). Kaplan–Meier survival analysis revealed that HCC patients with high expression of miR-18a possessed a more unfavorable prognosis (log-rank P<0.001). Overexpression of miR-18a promoted cell apoptosis and proliferation, induced S phase transition, as well as enhanced the migration and invasion ability of HCC cells. miR-18a was found to directly target the downstream molecule Bcl2L10. Furthermore, overexpressing Bcl2L10 was able to partly reverse the promoting effects of miR-18a on HCC cell progression.Conclusion: miR-18a may serve as a prognostic biomarker of HCC as it is demonstrated to carry out a decisive role in HCC progression by promoting HCC cell invasion, migration, and proliferation through targeting Bcl2L10. Keywords: miR-18a, hepatocellular carcinoma, Bcl2L10, apoptosis, cell cycle